2018
DOI: 10.2169/internalmedicine.0118-17
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure with Hyperthyroidism Demonstrating Discrepancy between the Clinical Course and B-type Natriuretic Peptide Levels

Abstract: A 35-year-old Japanese man was emergently admitted to our hospital with chief complaints of palpitation and dyspnea. He has been treated for Basedow's disease. He was diagnosed with acute decompensated heart failure, atrial fibrillation and thyrotoxicosis. We started anti-thyroid agents and a treatment for heart failure with beta blockers and diuretics under anti-coagulation therapy. His B-type natriuretic peptide levels remained high, although the heart failure had been compensated and the heart rate was well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Prior studies have also shown a correlation between BNP levels and thyroid levels in patients without heart failure or cardiac disease [31,32]. BNP level was found to be 4-fold higher in patients with hyperthyroidism than in patients in a euthyroid state.…”
Section: Hyperthyroidism and Brain Natriuretic Peptide (Bnp)mentioning
confidence: 67%
See 1 more Smart Citation
“…Prior studies have also shown a correlation between BNP levels and thyroid levels in patients without heart failure or cardiac disease [31,32]. BNP level was found to be 4-fold higher in patients with hyperthyroidism than in patients in a euthyroid state.…”
Section: Hyperthyroidism and Brain Natriuretic Peptide (Bnp)mentioning
confidence: 67%
“…It is postulated that THs may stimulate the secretion of BNP, in addition to the main physiologic process: stimulation via stretching of the atrial myocardial tissue. Prior studies have shown that free T3 hormone directly stimulates the secretion of BNP from myocardial cells by increasing gene expression [31,33,34].…”
Section: Hyperthyroidism and Brain Natriuretic Peptide (Bnp)mentioning
confidence: 99%
“…Within the scenario of acute exacerbation, the measurement of serum natriuretic peptides is useful, particularly in scenarios of patients with multiple comorbidities whose main symptom is dyspnea. Elevated BNP or NT-proBNP values are consistent with the cardiac etiology of dyspnea and are also usefulness as prognostic markers [ 69 , 70 ]. The use of other imaging aids, such as magnetic resonance imaging, for the diagnosis of heart failure has also been reported; however, these techniques are not generally available and have high costs, and their use is not standardized [ 71 ].…”
Section: Hyperthyroidism and Heart Failurementioning
confidence: 99%
“…It was noted that FT3 has a direct stimulus for the BNP secretion from myocardial cells by increasing the gene expression. Thus, THs in a direct action increase myocardial BNP gene expression 57,58 .…”
Section: Introductionmentioning
confidence: 99%